ULTRASTRUCTURAL CHANGES OF THE RAT CONTRACTILE MYOCARDIAL APPARATUS DURING PRENATAL ONTOGENESIS IN NORM AND AFTER ALCOHOL INFLUENCE - Tverdokhlib, I.V.; Marchenko, D.G. (World of Medicine and Biology, 2019)
Information on the formation of the contractile apparatus of the heart and the distribution of myofibrils in cardiomyocytes under conditions of intrauterine intoxication with ethanol remain a subject of considerable debate. The aim of the study was to determine changes in the ultrastructure of the contractile apparatus of rat ventricular cardiomyocytes during prenatal development in conditions of intrauterine alcohol intoxication. It was determined that chronic alcohol intoxication in prenatal cardiogenesis damages the contractile apparatus of ventricular cardiomyocytes due to disorganization of the structure of sarcomeres, fragmentation and disorientation of myofibrils, significant inhibition of sarcomere genesis, and a decrease in the content of myofibrils, which is associated with destruction of mitochondria. The severity of changes in these structures depends on the zone and period of development of the embryo. The most significant changes are due to the direct toxic effect of ethanol and occur in the early stages of cardiogenesis.